2018
DOI: 10.1016/j.firesaf.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of the interaction between water sprays and hot air jets - Part II: Two-phase flow simulations

Abstract: The paper presents a comprehensive set of numerical simulations performed to examine the current Computational Fluid Dynamics (CFD) capabilities in the prediction of the interaction of a water mist spray with a vertical upward jet of hot air within an Eulerian-Lagrangian framework. The experimental tests

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The study identifies the momentum ratio of hot air to spray, droplet size variation and volume flux due to water evaporation as key parameters that define plume-spray interaction. Similarly, Beji et al 48 also reported a reduction in the maximum ceiling jet velocity by 50%, while increase in ceiling layer thickness observed was also four times for the vertical jet-dominated spray regimes. The three regimes of spray-jet interaction (i.e.…”
Section: Interaction Of Sprinkler Spray and Stratified Hot Air Layer (Fire Plume)mentioning
confidence: 63%
“…The study identifies the momentum ratio of hot air to spray, droplet size variation and volume flux due to water evaporation as key parameters that define plume-spray interaction. Similarly, Beji et al 48 also reported a reduction in the maximum ceiling jet velocity by 50%, while increase in ceiling layer thickness observed was also four times for the vertical jet-dominated spray regimes. The three regimes of spray-jet interaction (i.e.…”
Section: Interaction Of Sprinkler Spray and Stratified Hot Air Layer (Fire Plume)mentioning
confidence: 63%
“…The settings for the base case are reported in Table 3. The initial velocity was calculated as: (7) where ρd is the water density (1000 kg/m 3 ) and ΔPw is the operational pressure of the nozzle. The constant C accounts for friction losses in the nozzle, estimated as C = 0.95.…”
Section: Water Mist Spraymentioning
confidence: 99%
“…Therefore, Computational Fluid Dynamics (CFD) simulations are a very useful 'support' tool in this context. In [6] and [7], e.g., the influence of a water mist spray on the ceiling-jet underneath a horizontal ceiling plate, created by a vertical upward jet of hot air, was reproduced very well. In [8], it has been reported that the heat release rate (HRR) instantaneously increased by the water mist flow just before rapidly decreasing because the high-speed water mist jet flow pushed the fuel vapor to the side.…”
Section: Introductionmentioning
confidence: 96%
“…As an alternative, Computational Fluid Dynamics (CFD) codes have become important tool during the past decades, due to the increasing computional resources and due to the development of scalable CFD solvers (e.g, OpenFOAM R 2.4.0 [26] used in this study). Furthermore, the need for accurate simulation results of turbulent two-phase, dispersed flows, that can capture the complexity of the flow field within acceptable computational costs, has led to a significant interest in Large Eddy Simulations (LES) [16], [1], [14], [11].…”
Section: Introductionmentioning
confidence: 99%